The Effect of Using Online Reading Resources toward Students' Reading Comprehension in Extensive Reading Class - estika satriani (J-SHMIC : Journal of English for Academic, 2017)
The students at the Second Semester of English Study Program of FKIP-UIR Pekanbaru have problem in reading comprehension. The aim of this research is to find out whether Online Reading Resources has significant effect towards students’ reading comprehension in extensive reading class. The design of the research was experimental research which focused on quantitative approach. The participants of the research were the second semester students of English Study Program of FKIP-UIR Pekanbaru. There are two classes as the samples of this research; experimental group and control group. Each of the group consisted of 31 students. The instruments of this research was reading test. Experimental group was provided with pre-test, treatment, and post-test. Meanwhile control group only given pre-test, and post-test. The finding showed that the mean score in pre- test was 57.25 and post test was 78.07, the improvement was 20.8 for experimental group. Meanwhile for control group in pre-test, the students got the mean score 58.07, and in post-test got 64.67, improvement was 6.61. It could be stated that there is significant effect of online reading resources after getting treatment. In calculation of analysis tt (t table) on the level of significant 5% found 0.361, and to was 7.1. It could be seen a comparison was 7.1>0.361or (to>tt). It means that the null hypothesis is rejected and alternative hypothesis is accepted. It can be stated there is a significant effect of students’ reading comprehension in extensive reading class after using online reading resource in teaching and learning reading at the second semester of English Study program FKIP-UIR Pekanbaru.